MOTIF PENGGUNAAN RADIO MORA OLEH KOMUNITAS PENDENGAR AMOR DI KOTA BANDUNG JAWA BARAT - Henny Sri Mulyani R (Avant Garde, 2018)
The power of the radio is based on the direct power, penetration, and attraction of the ra-dio. Radio trends today have a specific segmentation or type of format based on a particu-lar content selection. In turn make the radio station has its own trademark. Radio Mora is one of the radio media that has specific content that is about the law information as the main menu of the broadcast. Community listeners of Mora Radio named Members of Mo-ra (Amor). The existence of this community shows that they consciously have a motive in using the media in addition to other media for the fulfillment of information needs. There-fore, the researcher is interested to see how the motive use of Mora radio media by Amor community to meet the information needs in the field of law. The research method used is descriptive quantitative. The results show that Amor community members have an infor-mation motive consisting of looking for news, getting guidance, knowing various opinions, studying law with very high category. Motives of personal identity include consisting of finding behavioral models, improving self-understanding, supporting personal values are high. Motives of interaction and social integration consist of knowing other people's cir-cumstances, finding chats, helping social roles, connecting with society etc. As well as the motive of entertainment consists of forgetting the daily problems, relax, enjoyment of the soul, fill the spare time and distribute emotion quite high.